Pathogenesis of periodontal disease - Literature review (Research, Society and Development, 2025)
Introduction: Periodontal collapse will result in gingivitis and / or periodontitis. Inflammatory and immune reactions to the dental biofilm are its predominant findings. Such a reaction is clinically and microscopically visible in the affected periodontium. Understanding the mechanisms that govern the pathogenesis of periodontal diseases is a decisive factor in taking effective measures to control the disease. Theoretical Background and Discussion: Healthy periodontal tissues demonstrate structural and physiological protective signals. When bacterial components interact with the epithelium and are able to penetrate the connective tissue, an immune-inflammatory response of the host begins. If the microbial challenge remains unchanged, the inflammatory process will increase in the region. The conditions within the dental biofilm that is forming begin to favor the succession of bacterial species and lead to micro and macroscopic alterations of the periodontal tissues, which will be the result of the interaction between the microorganisms present in this biofilm and the tissues and inflammatory cells of the host. Methodology: Narrative review of literature on the immuno-biological mechanisms that involve the pathogenesis of periodontal disease. The search for the articles was carried out in the databases PubMed, Bireme and Scielo and the following descriptors: pathogenesis, dental biofilm, periodontal disease. Conclusion: The dental biofilm is fundamental to the beginning of the pathological process. It alone does not explain the variety of disease stages. So questions about the individual's immune susceptibility may be the complementation of the response. Thus, the planning of periodontal treatment should be based on the scientific basis.